Coseismic slip and afterslip of the Great Mw 9.15 Sumatra-Andaman earthquake of 2004 - Chlieh, Mohamed (2012)
We determine coseismic and the first-month postseismic deformation associated with the Sumatra–Andaman earthquake of 26 December 2004 from near-field Global Positioning System (gps) surveys in northwestern Sumatra and along the Nicobar-Andaman islands, continuous and campaign gps measurements from Thailand and Malaysia, and in situ and remotely sensed observations of the vertical motion of coral reefs. The coseismic model shows that the Sunda subduction megathrust ruptured over a distance of about 1500 km and a width of less than 150 km, releasing a total moment of 6.7–7.0 × 10^22 N m, equivalent to a magnitude Mw ∼9.15. The latitudinal distribution of released moment in our model has three distinct peaks at about 4° N, 7° N, and 9° N, which compares well to the latitudinal variations seen in the seismic inversion and of the analysis of radiated T waves. Our coseismic model is also consistent with interpretation of normal modes and with the amplitude of very-long-period surface waves. The tsunami predicted from this model fits relatively well the altimetric measurements made by the jason and topex satellites. Neither slow nor delayed slip is needed to explain the normal modes and the tsunami wave. The near-field geodetic data that encompass both coseismic deformation and up to 40 days of postseismic deformation require that slip must have continued on the plate interface after the 500-sec-long seismic rupture. The postseismic geodetic moment of about 2.4 × 10^22 N m (Mw ∼8.8) is equal to about 30 ± 5% of the coseismic moment release. Evolution of postseismic deformation is consistent with rate-strengthening frictional afterslip.